KARAKTERISASI HASIL PEMURNIAN MINYAK HATI IKAN CUCUT PISANG (Charcharinus falciformis) - Anhar Rozi (Universitas Teuku Umar, 2017)
The shark has a yield by-product from its liver up to 20% of its body weight, 50% of the total fish oil found on the liver. The aimed of this study was utilized by-product from shark’s liver oil and neutralization it to improve its quality shark liver oil. The method of quality fish oil referred to AOAC. The treatments in this study was extraction with temperature 50 °C and bleaching using magnesol XL 3%. The result of showed that the bleaching using magnesol XL can affect quality of silky shark liver oil. The result refined oil using magnesol XL 3% did not contain any microbes. Refined method using magnesol 3% produced oil with quality value (FFA: 0,72%±0,06; PV: 1,27±0,04 mEq/kg; p-AV: 4,27±1,95 mEq/kg; TOTOX: 7,27±1,93 mEq/kg; AV: 0,74±0,00 mg KOH/kg; clarity: 74,19±1,7 %).